Risk factors for recurrent biliary obstruction following placement of self-expandable metallic stents in patients with malignant perihilar biliary stricture - Miura, Shin; Kanno, Atsushi; Masamune, Atsushi; Hamada, Shin; Hongou, Seiji; Yoshida, Naoki; Nakano, Eriko; Takikawa, Tetsuya; Kume, Kiyoshi; Kikuta, Kazuhiro; Hirota, Morihisa; Yoshida, Hiroshi; Katayose, Yu; Unno, Michiaki; Shimosegawa, Tooru (Endoscopy, 2016)
Background and study aim: Self-expandable metallic stents (SEMSs) are used for palliation in patients with malignant perihilar biliary strictures. However, recurrent biliary obstruction occasionally causes cholangitis and jaundice. This study aimed to identify risk factors for recurrent biliary obstruction in such patients.Methods: Data from consecutive patients with malignant perihilar biliary strictures treated with endoscopic placement of SEMSs between 2007 and 2014 in Tohoku University Hospital were retrospectively reviewed. Risk factors for recurrent biliary obstruction were calculated using the Cox proportional hazards models (with hazard ratios [HRs] and 95 % confidence interval [95 %CIs]), and SEMS patency period was examined using the Kaplan – Meier method. SEMS patency was defined as the period between SEMS insertion and the development of recurrent biliary obstruction.Results: 104 patients were included. Median survival time was 281 days; and 85 patients died during a median follow-up period of 320 days. Recurrent biliary obstruction occurred in 35 patients. Median SEMS patency period was 549 days. Multivariable analyses showed that: compared with bile duct carcinoma, gallbladder carcinoma was associated with shorter SEMS patency (HR 8.18, 95 %CI 2.41 – 26.83); patency of left-sided SEMS was inferior to that of bilateral (HR 0.5, 95 %CI 0.32 – 0.93) and right-sided SEMS (HR 0.1, 95 %CI 0.02 – 0.65). Cholangitis before SEMS placement increased the risk of recurrent biliary obstruction (HR 11.44; 95 %CI 4.48 – 32.35) and reduced the SEMS patency period (746 vs. 210 days). Conclusion: Gallbladder carcinoma, left-sided stent placement, and cholangitis before SEMS placement are risk factors for recurrent biliary obstruction after SEMS placement.